Optimizing Heart Failure Management: A Review of the Clinical Pharmacist Integration to the Multidisciplinary Health Care Team - Zavaleta Monestel, Esteban (2023)
Heart failure (HF) stands as a prevalent chronic ailment, imposing a substantial burden on global healthcare systems due to recurrent hospitalizations, intricate management, persistent symptoms, and polypharmacy challenges. The augmentation of patient safety and treatment efficacy across various care stages, facilitated by a multidisciplinary HF team inclusive of a clinical pharmacist, emerges as paramount. Evidence underscores that the collaborative engagement of a physician and a clinical pharmacist engenders proficient and secure management, forestalling avoidable adversities stemming from drug reactions and prescription inaccuracies. This synergistic approach tailors treatments optimally to individual patients. Post-discharge, the vulnerability of HF patients to re-hospitalization looms large, historically holding sway as the foremost cause of 30-day readmissions. Diverse strategies have been instituted to fortify patient well-being, leading to the formulation of specialized transitional care programs that shepherd patients effectively from hospital to outpatient settings. These initiatives have demonstrably curtailed readmission rates. This review outlines a spectrum of roles assumed by clinical pharmacists within the healthcare cohort, spanning inpatient care, transitional phases, and outpatient services. Moreover, it traverses a compendium of studies spotlighting the affirmative impact instigated by integrating clinical pharmacists into these fields.